Highly silicic glasses in peridotite xenoliths from Avacha volcano, Kamchatka arc; implications for melting and metasomatism within the sub-arc mantle - Ishimaru Satoko; Arai Shoji (My University, 2009)
Silicate glasses in peridotite xenoliths from Avacha volcano have high SiO2 (up to 72 wt.) and highly SiO2-oversaturated characteristics; normative quartz content is up to 50 wt.. The glasses represent secondary melts solidified after interaction with mantle peridotite, i.e. crystallization of secondary orthopyroxene at the expense of olivine. We identified two kinds of silicate glasses in Avacha peridotites; one is higher in K2O and enriched in Rb, Ba, U, and Pb than the other. The glasses show basically similar chemical characteristics to the host basaltic andesite to andesite of the Avacha volcano. These chemical characteristics are inherited from slab-derived fluids/melts, which metasomatize the mantle wedge and induce partial melting. The differences of chemical features among the Avacha glasses are attributed to chemical difference of the slab-derived fluids/melts, possibly due to the difference of sediments/basalt ratio of the relevant slab. The low-degree partial melt of peridotite assisted by these fluids/melts, is primarily SiO2-oversaturated, and can conduct silicate metasomatism, evolving through interaction with surrounding mantle peridotite, i.e. formation of orthopyroxene at the expense of olivine. Highly silicic glasses, also reported from peridotite xenoliths from oceanic hotspots and continental rift zones, mostly result from assimilation of orthopyroxene by SiO2-undersaturated melts, which crystallize clinopyroxene and olivine. The glasses also show similar trace-element patterns to their host alkali basaltic magmas, as in the case of arc glasses/calc-alkali magmas. If the glasses in peridotite xenoliths are of silicate metasomatism origin, they are similar in chemistry to host magmas. Reaction between carbonatite melts and peridotites shows the same petrographical feature as that of SiO2-undersaturated silicate melts with peridotites. The glasses originated from carbonatite metasomatism, however, exhibit clearly different trace-element patterns from their host alkali basaltic magmas.
Keywords: 38.37.25 Вулканология; Авачинский